Studi Persebaran Kontaminan Lindi Dalam Air Tanah di Sekitar Lokasi Tempat Pemrosesan Akhir (TPA) - syahriawati, retno; Mulananda, Arisessy Maharani; Mahmudah, Norma; Sulaeman, Yulia Azizah (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), Politeknik Negeri Cilacap, 2025)
The waste in final disposal site that are not managed properly will have an impact the environment and human health. Leachate from rainwater infiltration or waste decomposition can contaminate groundwater due to leachate seepage into the soil. This research aims to determine the pattern of leachate contaminants migration and to predict the leachate contaminant in groundwater from wells of residents living near the landfill over a certain period. The method used is the Domenico analytical solution, where contaminant transport is influenced by advection, dispersion, retardation, and degradation. Source concentration of model simulation from laboratory tests of leachate samples where COD is 4,960 mg/L, hexavalent chromium is 3.5 mg/L, dissolved lead is 0.034 mg/L, and dissolved aluminium is 1.3 mg/L. The distribution pattern of leachate contaminants shows that the distribution of COD contaminants reaches ± 370 m in the longitudinal direction and ± 100 m in the transverse direction, while the distribution pattern of metal contaminants reaches ± 230 m in the longitudinal direction and ± 70 m in the transverse direction. When variations in the operational age of a landfill are 10, 25, and 50 years, the contaminant content of COD, hexavalent chromium, and aluminium exceeds the required quality standard thresholds, while lead is still within the required quality standard thresholds based on PP Nomor 22 Tahun 2021 (Kriteria Mutu Air Kelas II). Keywords: landfill, leachate, groundwater, analytical solution, contaminant transport.